PENGARUH STRATEGI COPING TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA KARYAWAN PT. NUTRINDO FRESHFOOD INTERNASIONAL - Merry Christi Makikama, Theisya; Endang Hartati, Meike; Becher Sengkey, Stevi (Penerbit Lafadz Jaya, 2025)
This study examines the effect of coping strategies on psychological well-being among employees of PT. Nutrindo Freshfood Internasional using a quantitative approach with 158 respondents from a population of 288 employees. Coping strategies comprise three main aspects: problem-focused coping, emotion-focused coping, and less useful coping, measured via modified Brief COPE and Ryff scales. Simple linear regression analysis reveals a significant positive effect of overall coping strategies on psychological well-being (regression coefficient 0.416; sig. 0.002 < 0.05), contributing 5.9%. In detail, problem-focused coping provides the largest contribution (22.5%; β=2.142; sig. 0.000), followed by emotion-focused coping (4.1%; β=0.634; sig. 0.011), while less useful coping is insignificant (0.8%; β=-0.369; sig. 0.256). Data satisfy normality (sig. 0.200) and linearity tests (sig. 0.712), with respondents dominated by females (65.2%) and ages 26-35 (40.5%). These findings underscore the role of problem-focused coping in enhancing psychological well-being in workplaces, aligning with prior studies like Rachmawati & Siregar (2021). Recommendations include problem-solving training for employees and future research incorporating moderators.